Staphylococcus aureus coa gene sequence analysis can prevent misidentification of coagulase-negative strains and contribute to their control in dairy cow herds - Locatelli, Clara; Gattolin, Stefano; Monistero, Valentina; Castiglioni, Bianca; Moroni, Paolo; Addis, Maria Filippa; Cremonesi, Paola (Frontiers in Microbiology, 2023)
Accurate and precise differentiation of staphylococci isolated from milk is of importance for udder health management. In particular, the rapid and specific identification of Staphylococcus aureus plays an essential role in the prevention and treatment programs for bovine mastitis. Plasma gelatinization in coagulase assays is routinely used to discriminate S. aureus from other species by detecting the presence of extracellular free staphylocoagulase. However, rarely occurring coagulase-deficient S. aureus strains can be responsible for clinical and subclinical mastitis cases. By investigating S. aureus isolates from a single herd over a 10-year period we identified the persistence of a phenotypically coagulase-negative S. aureus strain and pinpointed the possible cause to a single base pair deletion in the coa gene sequence. Our results support the need to integrate primary biochemical tests with molecular/sequence analysis approaches for correctly identifying and discriminating atypical S. aureus in bovine herds, as the coagulase test alone may fail to detect persistent mastitis-causing strains.